I love Lucy. The complete first season - Daniels, Marc; Oppenheimer, Jess; Davis, Madelyn Pugh; Carroll, Bob; Ball, Lucille, 1911-1989; Arnaz, Desi, 1917-1986; Vance, Vivian; Frawley, William, 1887-1966; Desilu Productions (Hollywood, CA : Paramount, 2005)
A domestic comedy featuring Lucy Ricardo, her bandleader husband and their neighbors.
The girls want to go to the nightclub -- Be a pal -- The diet -- Lucy thinks Ricky is trying to murder her -- The quiz show -- The audition -- The séance -- Men are messy -- Drafted -- The fur coat -- Lucy is jealous of girl singer -- The adagio -- The benefit -- The amatuer hour -- Lucy plays cupid -- Lucy fakes illness -- Lucy writes a play -- Breaking the lease -- The ballet -- The young fans -- New neighbors -- Fred and Ethel fight -- The moustache -- The gossip -- Pioneer women -- The marriage license -- The kleptomaniac -- Cuban pals -- The freezer -- Lucy does a TV commercial -- The publicity agent -- Lucy gets Ricky on the radio -- Lucy's schedule -- Ricky thinks he is going bald -- Ricky asks for a raise.
Features: flubs, deleted scenes, original series opening, production notes, scene access, guest star information, Lucy's radio show.
Production credits vary by episode.
Lucille Ball, Desi Arnaz, Vivian Vance, William Frawley.
Originally broadcast on television 1953-1954.
MPAA rating: Not rated.
DVDs, Dolby digital mono.
Keywords: Husband and wife -- Drama; Families -- Drama; Television programs; Video recordings for hard of hearing people; Comedy television programs